Provision of Public Goods by Social Enterprises - an Outline of the Issues - Hnatyszyn-Dzikowska, Anna (Studia Oeconomica Posnaniensia, 2015)
The role of social enterprises in the economy can be defined as multidimensional. Firstly, they are considered as the key subject wherever market failure, as well as the failure of the government occurs. Secondly, they act as a partner for the public sector by reducing its reliance on such enterprises in providing public goods. These roles complement each other to form a new means of meeting social needs. It is hard to imagine a modern society without public goods, which include not only infrastructure but also education and healthcare. However, the efficient and effective provision of social enterprises must meet the basic conditions which, as shown by the analysis carried out in the article, are still not fully taken into account in Poland. The literature reviewed indicates the key challenges which include: clarifying the cooperation framework (competences, responsibilities) between social enterprises , the public sector and beneficiaries; improvements to the legal system governing the operation of social enterprises; strengthening their organizational mechanisms and increasing interest from political authorities. These activities will allow the various needs of the consumption of public goods; increasing and diversifying of sources of financing public goods to be satisfied; reduce costs and improve productivity and the level of distribution of public goods, as well as a focus on the interests of vulnerable groups.